2018
DOI: 10.3390/agriculture8060082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Error in the Use of Agricultural Tractors: A Case Study Research in Vineyard Cultivation in Italy

Abstract: Recently, standards and regulations concerning occupational safety have become more and more rigorous. Nevertheless, the number of accidents and victims has not decreased significantly, as reported by official statistics. In Italy, the agricultural sector is certainly one of the most affected by this situation, especially taking into account the occurrence of serious injuries and fatalities related to the use of tractors. The main reasons for such a situation can be ascribed to the peculiarities of agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 79 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…In order to deal with such a complexity, Mitropoulos et al [7] highlighted the need of analyzing the characteristics of working tasks, given that the normative approaches hardly consider the characteristics of the working processes in a proper manner. As a matter of fact, the improvement of human safety relies on the reduction of the risks for the workers when performing specific working activities considering human factors [8]. Accordingly, specific work situations should be considered with more attention, since ensuring the safety of the various tasks is the precondition for ensuring a higher level of safety from both a project and an operative perspective [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to deal with such a complexity, Mitropoulos et al [7] highlighted the need of analyzing the characteristics of working tasks, given that the normative approaches hardly consider the characteristics of the working processes in a proper manner. As a matter of fact, the improvement of human safety relies on the reduction of the risks for the workers when performing specific working activities considering human factors [8]. Accordingly, specific work situations should be considered with more attention, since ensuring the safety of the various tasks is the precondition for ensuring a higher level of safety from both a project and an operative perspective [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, awareness of occupational health and safety (OHS) issues has increased worldwide thanks to both the efforts made by national and international legislators, who have developed stricter and more thorough normative frameworks, and the spread of new approaches to safety problems in workplaces relying on "safety culture" and "safety management" concepts [1][2][3][4]. However, the number of occupational accidents and fatalities is not decreasing sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…In the agricultural field, several studies have investigated the safe behavior and risk perception of farmers. The human factors leading to accidents while using tractors were investigated by means of a task analysis approach, providing information of the farmers' safety attitude and behavior when dealing with this type of machinery [26]. Other studies have focused on the farmers' risk perception by means of scenarios related to the use of machinery and describing a real-life working situation [27]; the results showed that the farmers were aware of certain types of risks, particularly when these were associated to economic losses.…”
mentioning
confidence: 99%